A Mitigation Technique to Reduce Ground Settlements Induced by Tunnelling Using Diaphragm Walls. (2016) - Fantera, Laura; Rampello, Sebastiano; Masini, Luca
Abstract: Ground movements due to the excavation of shallow tunnels may cause damage or loss of functionality to nearby buildings: embedded diaphragm walls pre-installed between the tunnel and the building can be effective in reducing these movements thus preventing damage on existing structures. Plane strain finite element analyses are first presented in the paper in which a continuous diaphragm made by adjacent panels was modelled to evaluate the effects of different geometrical and mechanical parameters. For a limited set of these parameters, 3D FE analyses were also performed maintaining a plane strain excavation scheme to evaluate the effectiveness of an infinite diaphragm made by closely spaced piles. A 3D study is finally presented in which the horizontal diaphragm length needed to attain the same efficiency provided by an infinite diaphragm is evaluated. Completion of tunnel construction was assumed in both 2D and 3D studies.